2005
DOI: 10.1128/mcb.25.8.3076-3086.2005
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Neuronal Enhancers of the Proopiomelanocortin Gene by Transgenic Mouse Analysis and Phylogenetic Footprinting

Abstract: The proopiomelanocortin (POMC) gene is expressed in the pituitary and arcuate neurons of the hypothalamus. POMC arcuate neurons play a central role in the control of energy homeostasis, and rare loss-offunction mutations in POMC cause obesity. Moreover, POMC is the prime candidate gene within a highly significant quantitative trait locus on chromosome 2 associated with obesity traits in several human populations. Here, we identify two phylogenetically conserved neuronal POMC enhancers designated nPE1 (600 bp) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
115
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 82 publications
(121 citation statements)
references
References 69 publications
(77 reference statements)
6
115
0
Order By: Relevance
“…In previous work we defined nPE1 as a 630-bp human-mousedog conserved sequence able to direct reporter gene expression to hypothalamic POMC neurons of transgenic mice (15). Because the critical functional regions of cell-specific enhancers are usually under stronger selective constraint than neighboring nonfunctional regions, we performed an evolutionary divergence analysis to calculate the substitution rate along nPE1 sequences in every branch of a phylogenetic tree constructed from all available mammalian species ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In previous work we defined nPE1 as a 630-bp human-mousedog conserved sequence able to direct reporter gene expression to hypothalamic POMC neurons of transgenic mice (15). Because the critical functional regions of cell-specific enhancers are usually under stronger selective constraint than neighboring nonfunctional regions, we performed an evolutionary divergence analysis to calculate the substitution rate along nPE1 sequences in every branch of a phylogenetic tree constructed from all available mammalian species ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The physiological relevance of POMC-derived peptides in the brain can be readily appreciated in mice lacking central Pomc expression, which are hyperphagic and display earlyonset severe obesity (14). Transcriptional regulation of Pomc in neurons is conveyed by two upstream distal enhancers, named nPE1 and nPE2, which are highly conserved in mammals (15). Expression studies in transgenic mice showed that nPE1, as well as nPE2, is sufficient to independently drive reporter gene expression to POMC neurons when placed upstream of a minimal heterologous promoter (15).…”
Section: Convergent Evolution Of Two Mammalian Neuronal Enhancers By mentioning
confidence: 99%
See 2 more Smart Citations
“…Cooperative interactions between two POMC‐neuron‐specific enhancers, nPE1 and nPE2, promote expression of Pomc transcripts in the mouse ventromedial hypothalamus (Franchini et al., 2011; de Souza et al., 2005). Deletion of nPE2, nPE1, or insertion of a transcription‐blocking neo selection cassette into the vicinity of the two hypothalamic neuronal Pomc enhancers reduces hypothalamic Pomc expression to ~80%, ~30%, or ~2% of wild‐type controls, respectively (Lam et al, 2015).…”
mentioning
confidence: 99%